Study of von Willebrand Factor and Antithrombin III in Patients with Atherosclerosis - The Joint Study Unit of Atherosclerosis in Nationa (Japanese Journal of National Medical Services, 1988)
Eighty patients with atherosclerosis devided into 4 disease groups; acute myocardial infarction (AMI), previous myocardial infarction (MI), angina pectoris and cerebral infarction (CI), were studied and compared to 44 healthy subjects. Von Willebrand factor (vWF) was measured by modified Weiss method using fresh platelets, factor VIII coagulant activity (factor VIII) by one stage method and antithrombin III (AT III) activity by amidolytic method. Factor VIII and vWF were significantly (p<0.05) correlated with age. The mean vWF in patients with AMI, MI and CI was significantly higher than age matched healthy subjects. There was no significant difference in factor VIII between any group and healthy subjects. AT III was significantly lower (p<0.05) in patients with MI and CI than the healthy subjects. In AMI patients with abnormally high vWF, AT III was significantly lower (p<0.01) than healthy subjects. Perhaps, increased plasma vWF are associated with an increased risk of death from acute myocardial infarction and acute cerebral thrombosis. VWF may be a useful marker for development of atherosclerosis and predictor for the outcome of these diseases. Low antithrombin III activities in patients with atherosclerosis are perhaps due to consumption.